Assessing Tsunami Impacts and Enhancing Disaster Response in Tirtayasa Banten through High-Resolution Satellite Imagery - Junaid, Muhammad; Wibowo, Adi (MO.RI Publishing, 2024)
In December 2018, the coastal town of Tirtayasa, Banten, suffered severe damage from a tsunami, leaving the area highly vulnerable to future disasters. This research assesses the tsunami’s impact, thoroughly evaluating damage to infrastructure and vegetation using high-resolution satellite imagery. By comparing pre- and post-tsunami images, we quantitatively measure resilience and devastation, documenting significant landscape changes to better understand the extent of damage and identify resilient areas. These insights are critical for developing effective disaster response plans. The study employs advanced geospatial analytic techniques, demonstrating how satellite imagery enhances disaster preparedness and management by enabling prompt and accurate assessments, which are essential for both emergency response and long-term recovery planning. Integrating satellite-based remote monitoring into standard disaster management practices offers substantial advantages, improving the preparedness and response capabilities of vulnerable areas. This research highlights the importance of advanced change detection techniques to improve the accuracy of impact assessments and foster the development of targeted measures to mitigate the effects of future natural disasters.